Healthy ageing in India: strengthening community-based senior care beyond longevity - Karthikayini Sasinthar; K. P. Vishruth (International Journal Of Community Medicine And Public Health, 2026)
India is undergoing a profound demographic transition with a steady increase in the population aged 60 years and above. Declining fertility rates and improvements in life expectancy have reshaped the population structure, making older adults one of the fastest-growing demographic groups in the country.1,2 According to national projections, the ageing population is expected to continue expanding over the coming decades, creating substantial implications for healthcare systems, social protection mechanisms, and long-term care services. This demographic shift necessitates a transition from episodic, disease-centred healthcare toward integrated, person-centred approaches that preserve functional ability, independence, and overall wellbeing in later life.